Ethical inclusive curricula design: Conversational teaching and learning - Baron, P.R. (South African Journal of Higher Education, 2018)
South African Public Universities are facing transitional challenges as they traverse uncharted territory in decolonising knowledge. The idea of decolonising knowledge brings with it the need to review curricula as well as the lecturer’s pedagogy. A cybernetic approach using conversation theory is presented as a viable solution to inclusive and ethical contextual curricula design. Through conversation, contextual enquiries can be achieved which are then used as reference points in revising curricula. In this paper, a report back on a recent curriculum re-design is presented. The results of this process have been positive with students demonstrating increased participation, personal responsibility, and higher motivation in performing assignments. Other positive features are that students introduce new and relevant topics into the curriculum. These topics are contextualized by the students (and teacher) allowing for student interpretations of the content in terms of their daily lives, i.e. the students populate the curriculum with experiences they have had within their communities. There is increased social engagement in the classroom with students also dialoging in community with one another and the teacher. The abstraction of the curriculum is reduced in turn increasing the familiarity and personalization of the module content areas. This personalization effect was found to improve memory retention of the module content as the grades were higher for the topics that were proposed by students.